On Mλm,n-Statistical Convergence - Nazlım Deniz Aral; Şerife Günal (Journal of Mathematics)
In this paper, we introduce a new type of statistical convergence method for double sequences by using the M,λm,n-method of summability which was defined by Natarajan. We also obtain some inclusion relations between statistical convergence and Mλm,n-statistical convergence for double sequences.